БЕЗГРАНИЧЬЕ РЕАЛЬНОСТИ - Вандышева-Ребро, Н. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
В статье исследуются возможности и способы постижения реальности, которые демонстриру- ет нам опыт человечества. Мифологическое, религиозное, научное и модернистское сознание рассмат- ривается с точки зрения работы с действительностью. Человек, обнаруживший двусторонность своего бытия, вынужден постоянно работать над созданием другого мира. В этом и заключается особенность ситуации человека и его ценность как субъекта культуры. Вандишева-Ребро Н.В. Безмежжя реальності. У статті досліджуються можливості та способи осягнення реальності, які демонструє досвід суспільства. Міфологічна, релігійна, наукова та модерніст- ська свідомість розглядається з точки зору розуміння дійсності. Людина вже давно зрозуміла, що світ в якому вона існує двосторонній і треба багато та постійно працювати над створення другої реальнос- ті. Людина дійшла до визнання іншого (потойбічного) світу й відтоді змушена весь час його відбудову- вати у реальності. Автор статті саме в цьому вбачає особливість ситуації людини у всесвіті та її цін- ність як суб’єкта культури. Ключові слова: буття, реальність, дійсність, міфологія, модернізм, сюрреалізм. Vandysheva-Rebro Nadiya. The infiniteness of reality. The nature of man and the man himself to this day remains one of the extraordinary phenomenon. The ancient philosophers, and later European, followed by Socrates, set the tone and establish a tradition of European modern anthropology. However, until now, we cannot explore the nature of man in the same way as to reveal the nature of physical things. The physical world and the man developed a lot of energy spent on the study of this world – a world of reality. Thus, man and the world are forcedly interact with each other, and to understand reality we must start with the recognition of human vision. And just to understand the complex nature of the person, you can develop a system of beliefs about the world. A man is always in a search of himself, he is at every moment of its existence, experiencing and rechecks the condition of its existence. Inevitable moment of human nature comes to the realization that a person is not "nature" – a simple or homogeneous entity, with the result is a strange mixture of being and non-being, and its location – between these two poles. The structure of the human mind cannot be understood statically, because it is changing – narrows or expands – and depending on that person reveals different worlds. Truth reveals only when a person overcomes limitations. Until the 19th century, philosophers explored the world, but eventually new goals and objectives forms: to change the world, or create a new one. The emergence of modernism in general and in particular surrealism seems logical in this context and is quite lengthy and necessary cultural phenomenon. Exceptional sidedness makes life flat and get rid of it can only be abstracted and creating a new reality, which translates modernism as a worldview. Expectations were not disappointed – and a new way of thinking, which allowed without destroying the positive in society and without compromising existing natural and civilized environment comfortable enough to continue the existence of man kind. With the modernist worldview, a new fictional reality is being created. Man needs the diversity of worlds – it is a problem of the existence and understanding of infinity. Keywords: life, reality, reality, mythology, modernism, surrealism.